Developing a model for rating of Iranian banks based on soundness. - Mohammad Javad Salami; Mohammad Hasan Ebrahimi Sarvolia; Shiva Ghasempour (تحقیقات مالی, 2017)
This research aims to develop a domestic model to rank Iranian banks based on their function to evaluate soundness and stability. For this purpose, after studying the related literature, a model with six dimensions and thirty factors is designed and validated using Delphi-Fuzzy method. This resulted in a model with six dimension and twenty six factors. Then, using network analysis and applying Dematel technique, the final model and the weights of each factor were determined. We used the model to evaluate the performance of the several banks in year 1393. And then they were ranked by using TOPSIS technique. The results show that Pasargad, Khavarmiyane, Karafarin, Dey and Sina banks had better function in comparison to other studied banks in 1393..